The concise argument - Holm, S. (Journal of medical ethics, 2009)
Some new possible treatment modalities come with theoretical rationales for why they should be better than the current treatments. This theoretical promise of improvement over current therapy is often used to argue that we should implement the technology now and bypass all or some of the usual requirements for rigorous testing of new treatments. In a meticulously argued paper, Bjørn Hofmann uses the example of proton therapy, a new type of radiotherapy for solid tumours, to show the many ways in which such arguments can fail by invalidity or unsoundness (see p 684). He builds on a previous JME article by Holm and Takala,1 but extends the argument considerably by not only considering the ethical arguments that Holm and Takala considered but also considering epistemic and social arguments. It is impossible to mention all the many arguments that Hofmann dissects, but it is worth quoting his analysis of arguments built on the value of being progressive at some length to give a flavour of his analysis:“Correspondingly, a …